Czy to wszystko rodzina? Promocja tolerancji i edukacyjny aspekt biblioterapii a percepcja społeczna alternatywnych form życia małżeńsko-rodzinnego - Tomaszewska, Joanna (2016)
Diversity and pluralism in all spheres of postomdern life makes that social awareness of the fundamental values evolving and leading to a redefinition of basic concepts. Changes in the formation of marriage and the family are a particularly interesting aspect because it is strongly contrasting with the previous, traditional order and definitions, roles and functions of the family and set in the past. Permanent changes lead to a feeling of fear of the future where the anchoring is not possible and affect the development of new types of social attitudes that allow adapt to the present. Culture is, however, a dynamic and constantly reproduced force and therefore allows for adaptation to changing circumstances. It is particularly important understanding of diversity, nonconformist behaviors and intercultural education of children, which will constitute about the future of heterogeneous world. Presenting the children’s book „Alles Familie!” by Alexandra Maxeiner and Anke Kuhl. I would like to draw attention to the role it plays this type of transmission in the education of young citizens. Building a tolerant and accepts diversity society is the basis of today’s existence in the world.
Keywords: attitude; nonconformity; education; tolerance; postmodernism; family